The diabetes management self-efficacy scale: Translation and psychometric evaluation of the Iranian version - Azita Noroozi; Rahim Tahmasebi (Tehran University of Medical Sciences, 2015)
Background & Aim: Perceived self-efficacy could lead to self-management behaviors among diabetic patients and the Diabetes Management Self-efficacy Scale (DMSES) assesses the extent to which diabetic patients are confident that they can manage diabetes. However, the Iranian version of DMSES was not available. The objective of this study was the translation and psychometric evaluation of the Iranian version of the DMSES . Methods & Materials: Using a standard forward-backward translation procedure, the original English language version of the questionnaire was translated into Persian (Iranian language). Then, a convenient sample of diabetic patients, who referred to a diabetes outpatient clinic and were aged 15 to 81 years, completed the questionnaire. Validity was evaluated by content validity ratio and then using factor analysis. To test the reliability, internal consistency was assessed by Cronbach's alpha. Results: In total, 332 diabetic patients entered into the study. The mean age of respondents was 1.8 ± 12.3 years. Employing the recommended method of scoring (ranging from 1 to 5), the mean DMSES score was 2.24 ± 0.54. Reliability analysis showed satisfactory results (Cronbach's alpha = 0.92). Exploratory factor analysis showed 20 items of the scale could converge to 5 factors with rotation. Confirmatory factor analysis supported modified model of DMSES through which one item (item 20) moved from blood glucose factor to medical control factor. Criterion-related validity showed that the DMSES was a significant predictor of the diabetes self-management (R = 0.61; P < 0.001). Conclusion: The study findings showed that the Iranian version of the DMSES has a good structural characteristic and is a valid and reliable instrument that can be used for measuring diabetes management self-efficacy.